2020
DOI: 10.1371/journal.pone.0233217
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring a mobile health text-messaging intervention to promote antiretroviral therapy adherence among African Americans: A qualitative study

Abstract: African Americans are disproportionately affected by HIV and socio-structural barriers that impact antiretroviral (ART) adherence. Two-way text-messaging interventions have shown promise in supporting adherence in US studies of mostly White people living with HIV (PLWH). However, culturally-appropriate tailoring is necessary to maximize intervention effectiveness among other racial/ethnic groups. Thus, to refine an existing text-messaging intervention, we examined barriers and facilitators to ART adherence amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Previous studies have demonstrated the efficacy of 2-way SMS text messaging interventions in supporting ART adherence; however, these studies primarily enrolled non-Hispanic white PWH despite epidemiological evidence of greater HIV-related burden among African American PWH [ 25 ]. This protocol details the implementation of an intervention that was adapted using feedback from African American PWH and their providers of care [ 26 ]. We anticipate that the tailored iTAB intervention will significantly improve ART adherence among the targeted population and, consequently, could be implemented among other African American PWH across the state of California.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated the efficacy of 2-way SMS text messaging interventions in supporting ART adherence; however, these studies primarily enrolled non-Hispanic white PWH despite epidemiological evidence of greater HIV-related burden among African American PWH [ 25 ]. This protocol details the implementation of an intervention that was adapted using feedback from African American PWH and their providers of care [ 26 ]. We anticipate that the tailored iTAB intervention will significantly improve ART adherence among the targeted population and, consequently, could be implemented among other African American PWH across the state of California.…”
Section: Discussionmentioning
confidence: 99%
“…In formative study phases, issues arose related to integrating community-based participatory research with clinical practice. Focus group discussants suggested that the study facilitate interactions between patients and their providers of clinical care [ 26 ]. Thus, we aimed to provide study participants with the choice to share their iTAB adherence calendars with their providers to promote conversations around adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…“Culturally sensitive interventions are implicitly multicultural” as they seek to “incorporate and appreciate perspectives of multiple race/ethnic groups"(p. 11). 17 The implementation of culturally tailored content is not new and has proven to be cost-effective in promoting health behavior 32 ; academic literature has acknowledged the effectiveness in targeting minority populations under both positive (antiviral promotion; e.g., Pasipanodya et al 33 ) and negative (consumption of sugary snacks; Backholer et al 34 ) circumstances. Ryan et al 35 found that tailored interventions were more effective in influencing behavioral change and were rated by participants as more personally relevant, helpful, easier to understand, likely to be recommended to others, and novel than those in the non-tailored intervention group.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Technologies and innovative approaches are essential to maintaining patient-provider contact and offer a convenient method of communication. Health organizations have been utilizing mHealth platforms to reach and serve their respective communities (Pasipanodya et al, 2020). A review of HIV-focused social media interventions revealed increased access to information and enhanced ability to communicate (Cao et al, 2017).…”
mentioning
confidence: 99%